Doing Research in a Deployed Spoken Dialog System: One Year of Let's Go! Public Experience - Raux, Antoine; Bohus, Dan; Langner, Brian; Black, Alan W; Eskenazi, Maxine (Ninth International Conference on Spoken Language Processing (Interspeech 2006 — ICSLP), 2006)
This paper describes our work with Let’s Go, a telephone-based bus schedule information system that has been in use by the Pittsburgh population since March 2005. Results from several studies show that while task success correlates strongly with speech recognition accuracy, other aspects of dialogue such as turn-taking, the set of error recovery strategies, and the initiative style also significantly impact system performance and user behavior.